2009
DOI: 10.1186/1748-5908-4-44
|View full text |Cite
|
Sign up to set email alerts
|

Documenting the experiences of health workers expected to implement guidelines during an intervention study in Kenyan hospitals

Abstract: Background: Although considerable efforts are directed at developing international guidelines to improve clinical management in low-income settings they appear to influence practice rarely. This study aimed to explore barriers to guideline implementation in the early phase of an intervention study in four district hospitals in Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 32 publications
6
67
2
Order By: Relevance
“…This finding contradicts what was found by a Kenyan study [17], which established that health workers working in hospital paediatric departments were not cooperating and communicating openly with each other and this was affecting their performance and the quality of care given to patients. Some researchers have established that behaviours that involve cooperation, creativity and self-development contribute to job performance [28].…”
Section: Resultscontrasting
confidence: 93%
See 3 more Smart Citations
“…This finding contradicts what was found by a Kenyan study [17], which established that health workers working in hospital paediatric departments were not cooperating and communicating openly with each other and this was affecting their performance and the quality of care given to patients. Some researchers have established that behaviours that involve cooperation, creativity and self-development contribute to job performance [28].…”
Section: Resultscontrasting
confidence: 93%
“…This is contrary to what was found in Kenya where health workers were reported to have inadequacies in adapting or responding to new clinical practices or guidelines due to lack of perceived benefits linked to their uptake [17]. In that study, senior and older health workers were often reported to be stuck in the patterns of previous clinical practice although there were some exceptions [17]. This problem was attributed to the lack of experience in being compelled to change by emerging knowledge.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…the professional groups involved in the local process that resulted in the document accept it and are committed to its use), all of which are important for the successful implementation of guidelines. 38,39 For example, an Australian version is being prepared with permission from the authors and funders of the original United Kingdom version. It includes minor changes to the text and alternative suggestions for information resources.…”
Section: Discussionmentioning
confidence: 99%